Development of an amperometric sensor for potassium ions - Teixeira, Marcos F.S. [UNESP]; Lima, Alex S. [UNESP]; Seraphim, Patricia Monteiro [UNESP]; Bocchi, Nerilso (My University, 2008)
Hollandite-type manganese oxides are nanofibrous crystals with sub-nanometer open tunnels that provide a unique property for sensing applications. Sensor based on hollandite-type manganese oxide was investigated for amperometric detection of potassium. With an operating potential of +0.63 V versus SCE, potassium ions produce oxidation currents at the sensor, which can be exploited for quantitative determinations. The amperometric signals are linearly proportional to potassium ions concentration in the range 2.7 × l0-4 to 9.1 × l0-4 of with a correlation coefficient of 9990. The construction and renewal are simple and inexpensive.
Keywords: Hollandite; Sensor for potassiumions; Voltammetry